2021
DOI: 10.3390/nu13030730
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal Maternal Docosahexaenoic Acid (DHA) Supplementation and Newborn Anthropometry in India: Findings from DHANI

Abstract: Long-chain omega-3 fatty acid status during pregnancy may influence newborn anthropometry and duration of gestation. Evidence from high-quality trials from low- and middle-income countries (LMICs) is limited. We conducted a double-blind, randomized, placebo-controlled trial among 957 pregnant women (singleton gestation, 14–20 weeks’ gestation at enrollment) in India to test the effectiveness of 400 mg/day algal docosahexaenoic acid (DHA) compared to placebo provided from enrollment through delivery. Among 3379… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…The method described above is specific, accurate and precise and can be standardized with short training. The validated method has been used for the analysis of omega-3 and omega-6 fatty acids in DHANI study (Khandelwal et al, 2020, Khandelwal et al 2021. The method can also be used for evaluation of fatty acids in large nutritional trials and as biomarker assessment for large epidemiological studies.…”
Section: Resultsmentioning
confidence: 99%
“…The method described above is specific, accurate and precise and can be standardized with short training. The validated method has been used for the analysis of omega-3 and omega-6 fatty acids in DHANI study (Khandelwal et al, 2020, Khandelwal et al 2021. The method can also be used for evaluation of fatty acids in large nutritional trials and as biomarker assessment for large epidemiological studies.…”
Section: Resultsmentioning
confidence: 99%
“…In 1 trial, probiotics administration during pregnancy is associated with lower excessive weight-gain in 4-year-old children (13). However, not all studies have found associations between these supplements and child's growth, weight, or body composition (14)(15)(16). Fish oil and probiotics potentially have co-effects on maternal metabolism (17), but this view has not been yet studied with regards to child's growth.…”
Section: What Is Newmentioning
confidence: 99%
“…Khandelwal et al [ 4 ] reported the impact of maternal supplementation of 400 mg algal DHA/day on newborn anthropometry; appearance, pulse, grimace, activity, and respiration (APGAR) score; duration of gestation; and birth weight among Indian women. They supplemented women ( n = 478) from 14–20 weeks’ gestation till delivery in a double-blind, randomized, placebo-controlled (placebo; n = 479) trial in pregnant women.…”
mentioning
confidence: 99%
“…The mean gestational age at delivery and APGAR scores were similar between the two groups. They concluded that supplementing pregnant mothers with 400 mg/day DHA did not impact the offspring’s birth weight, length, or head circumference [ 4 ].…”
mentioning
confidence: 99%